Cost evaluation of different medium solids for air dense medium fluidized bed coal separation - Chagwedera, Kundayi Marshall (My University, 2017)
Dense medium processing of high ash coals with liquid dense media water and magnetite is currently the conventional means of beneficiating coal in South Africa SA. Hence, large volumes of waste water are produced along with a high cost of treating this effluent, both factors of which constitute a major disadvantage to this technique. This study presents an experimental account of Air Dense Medium Fluidized Bed ADMFB as an alternative dry processing approach for beneficiating SA coals. Magnetite is the conventional medium in ADMFB application this medium material is costly and limited in quantity. Pyrrhotite, granulated blast-furnace slag, silica sand and coal discards were investigated as alternative air dense medium materials to either replace or augment magnetite. Each of the materials utilized was prepared for a specific size range and characterised according to their physical properties. The materials were then tested individually, first as sole fluidized media followed by further tests where the materials were blended in various proportions. The purpose was to establish their fluidization characteristics and suitability for coal separation. Uniformity and stability of the bed density were considered the key performance parameters for facilitating coal quality separations and therefore these were used as the main criteria for selecting the potential best medium material. Initial beneficiation tests with density tracers in lieu of coal were used for the purpose of optimizing operating parameters and separation efficiency for each of the media utilized. Based on the results obtained from the trial tests, coal was then tested in the ADMFB fluidized bed separator. Magnetite and pyrrhotite, individually, provided the most uniform and stable bed densities with bed density variation and standard deviation.
Masters dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Engineering to Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, South Africa, 2017